If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(8 + 7f) = 5(-6 + -3f) (8 * 3 + 7f * 3) = 5(-6 + -3f) (24 + 21f) = 5(-6 + -3f) 24 + 21f = (-6 * 5 + -3f * 5) 24 + 21f = (-30 + -15f) Solving 24 + 21f = -30 + -15f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '15f' to each side of the equation. 24 + 21f + 15f = -30 + -15f + 15f Combine like terms: 21f + 15f = 36f 24 + 36f = -30 + -15f + 15f Combine like terms: -15f + 15f = 0 24 + 36f = -30 + 0 24 + 36f = -30 Add '-24' to each side of the equation. 24 + -24 + 36f = -30 + -24 Combine like terms: 24 + -24 = 0 0 + 36f = -30 + -24 36f = -30 + -24 Combine like terms: -30 + -24 = -54 36f = -54 Divide each side by '36'. f = -1.5 Simplifying f = -1.5
| 26x-13=13 | | 6d=d | | 371=-7(3+8x) | | 26x=2 | | -16=-8(10+b) | | 11/4w=33/5 | | 5n+4=35 | | 160=6(4n+6)+4 | | 4(2-4y)=8y+56 | | 75=3(1-4k) | | y+(-8)=8 | | 70=-5(3b-5) | | (9x+36)-(8x+1)=y | | 3-6y=-6y-3 | | 5a+18=2a | | -6(3-2x)=-90 | | (9x+36)-(8x+1)= | | 4s^2-36s+81=0 | | 8(2w+3)=4(3w-2) | | 9(4x-2)=54 | | 2(b-3)+b=3(2x-10) | | 34m+14=30m+8 | | b=2x-8 | | 5x+1=-7x+121 | | 5(x+9)-8=-19 | | -8=-8(6p-5)+10(2+4p)+10p | | x+4=5x+12 | | 3(z-2)-1=4(z-3) | | 3x+1-5=2x+4 | | 16=-4+5y | | 2x^2+5x-3=7x+9 | | 8.3+0.7=8.3 |